THE IMPACTS OF ANXIETY AND SELF-EFFICACY BELIEFS OF STUDENTS ON THE ACHIEVEMENT LEVELS ABOUT READING AND INTERPRETATION OF GRAPHS - HALAT, Erdoğan; ÇİMENCİ ATEŞ, Firdevs (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The aim of this study was to examine the effects of anxiety and self-efficacy beliefs of the eighth grade students on the achievement levels about the reading and interpretation of the frequency polygon and histogram. There were a total of 388 eighth grade students involved in this study. They attended to the study from four different middle schools. The researchers used three different instruments in the collection of the data. One of the instruments was a multiple choice statistics test that included 22 questions about the reading and interpretation of graphs and finding of the measures of both central tendency and dispersion. This test was developed by the researchers who piloted it and found its reliability of Cronbach's alpha value as 0.80. The researchers also used a math anxiety scale developed by Şentürk (2010) and a math self-efficacy beliefs scale developed by Umay (2002) in the study. After the collection of the data, the researchers employed the paired samples t-test, independent samples t-test and two-way ANOVA in the analysis of the data. The study demonstrated that the anxiety and self-efficacy levels of the 8th grade students in mathematics had considerable effects on the students’ achievement levels about the reading and interpretation of the frequency polygon and histogram. The study also indicated that there were positive relationships between the students’ self-efficacy levels and the overall test scores. Furthermore, when their achievement levels were examined according to their anxiety levels, the achievement levels of the students on the test were found successively medium, low and high. The interaction of students’ anxiety and self-efficacy levels did not influence the accomplishment levels of the students about the reading and interpretation of the graphs.